Indonesia's Blue Economy Potential: Salt Pond in Nagekeo, East Nusa Tenggara - Salsabila Cherish Okcavia; Rudiyanto Rudiyanto; Panji Suwarno; Pujo Widodo; Herlina Juni Risma Saragih (CV. Rayyan Dwi Bharata, 2022)
Allegedly, based on the diversity of the maritime by Indonesia, our country has a very potential wealth of marine resources. These resources can be utilized for its used as blue econommy approach. This country’s marine resources that can be utilized as a national economic potential is a salt industry. With the wealth of the saline water that we have, Indonesia is still importing salt because there is an imbalance between demand and domestic production. The purpose of this journal is to find out the potential for briny ponds in Indonesia to be used to reduce the dependence on national imports. To handle this problem, there are several efforts to maximize our national productions of saline pond in Nagekeo District, East Nusa Tenggara (Nusa Tenggara Timur). Along with the modernization and technology, there is several branches of innovation and technology to increase the effectiveness of Indonesia’s Sea Salt Industry such as Geomembrane Prism House, Vertical Axis Mill Pump, and the Smart House Salt Maker (SHASA). By adopting these technologies, it is expected that the production of marine salt farmers will be able to severely reduce salt imports and make Indonesia a successful and independent maritime country.